2014
DOI: 10.2478/s11756-013-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant communities preferences of terrestrial crustaceans (Isopoda: Oniscidea) in a protected coastal area of southeastern Sicily (Italy)

Abstract: Abstract:We studied the plant communities preferences of oniscidean isopods in a protected coastal area in southeastern Sicily that is characterized by ponds, dunes and rocky coast. In total, five sites were sampled between March 2003 and February 2004 using pitfall traps. A total of 7,326 specimens were found, belonging to 23 species. The vegetation analysis, using the phytosociological method, recognized a total of 11 types of plant communities, with specific ecological features. Measuring the species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Several papers have been published on isopod faunas in European wetlands (Tuf, ; Dias, Sprung & Hassall, ; Garcia, ; Messina et al ., , , ; Antonovic et al ., ). In Tunisia, diversity studies of terrestrial isopod communities inhabiting the supralittoral zone of wetlands effectively started with the work of Jelassi, Khemaissia & Nasri‐Ammar (); Jelassi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have been published on isopod faunas in European wetlands (Tuf, ; Dias, Sprung & Hassall, ; Garcia, ; Messina et al ., , , ; Antonovic et al ., ). In Tunisia, diversity studies of terrestrial isopod communities inhabiting the supralittoral zone of wetlands effectively started with the work of Jelassi, Khemaissia & Nasri‐Ammar (); Jelassi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Some illustrations made with the method of the present paper, were already published in other articles about terrestrial isopods: figure 1 in Medini-Bouaziz et al (2006); figure 2 in Montesanto et al (2007); figures 2, 3 in Montesanto et al (2008); figures 1–5 in Montesanto et al (2011); figures 1, 2 in Messina et al (2011); figure 1 in Messina et al (2012); figures 6, 7, and 9 in Montesanto et al (2012); figure 1 in Lupetti et al (2013); figures 2, 3 in Montesanto et al (2013); figures 1–6 in Messina et al (2014). Some indications about drawing terrestrial isopods for taxomomic papers are reported in Figure 7, whereas magnifications show the differences of the brush size for different anatomical parts.…”
Section: Resultsmentioning
confidence: 80%
“…This species can reproduce several times throughout its life (iteroparous), and its reproductive period varies depending on the geographic area: in France from June with a possible extension until August (Vandel, 1962), in Sicily from May to July (Messina, Montesanto, Pezzino, Caruso, & Lombardo, 2011;Messina, Pezzino, Montesanto, Caruso, & Lombardo, 2012) and in Israel in October (Warburg, 2013). A. officinalis commonly lives on sandy, silty-clayey or rocky substrates, and in environments populated by different plant communities (Messina et al, 2014). In 2015, a possible use of these animals as bioindicators of benzene was also reported (Agodi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%